(untitled) (Journal of Hama University, 2022)
To Compare between the effectiveness of the tell-play-do, direct observation and tell-show-do technique. The research sample consisted of 60 children in the age group 5-7 years, whose had no previous experience, they were rated as positive(+) or negative (-) based on Frankl behavior rating scale, whose needed conservative dental treatment, and they were divided into three groups: The first group is Direct Observation technique, the second group is Tell-Play-Do technique, and the third group is Tell-Show-Do technique, in all sessions we recorded a video to show it to an external monitor to record the evaluation according to the FLACC scale, in addition to physiological assessment by Pulse Oximeter. In our study, it was found that behavior modification using the Tell- Play- Do (TPD) technique was more effective than the Direct Observation (DO) technique and Tell-Show-Do (TSD) technique in reducing dental anxiety and increasing the level of cooperation for children with negative(-) behavior rating based on Frankl, that’s for the two scales we used